Da alienação ao reconhecimento: interfaces para visualização de transformações espaço-temporais - Thiago Alfenas Fialho (2018)
This research is based on the acknowledgment of a paradox: although the tools and techniques of urban planning and design are increasingly sophisticated, the physical environment of most cities goes from bad to worse. Roads built over streams, floods, soil sealing, landslides and other problems related to environmental degradation are progressively recurrent; parks and squares are evermore scarce, noise and visual pollution have intensified more and more, people occupy less and less the public spaces, among other factors. The text starts with a very brief genealogy of the design of cities between the sixteenth and twentieth centuries, which shows: the moment when cities starts to be projected, which projection techniques are the most recurrent and, mainly, the degree of intervention in the cities implementation sites and, finally, their impact on the quality of urban spaces. Because it is a long-term time scale, five iconic exploratory case studies were selected, that is, good representatives of the various stages of the process mentioned above. Therefore, there were chosen: Valletta, in Malta (XVI); Mexico City (XVII), Paris (XVIII), San Francisco (XIX) and Belo Horizonte (XIX-XX), which illustrate, mainly, drastic changes in hydrography and relief. Moreover, these processes, generally predatory, common to the five cities, appear to have contributed decisively to a widespread degradation of their natural environments. For this, visual reconstitutions were made in computational environment of their urbanization processes. Therefore, the dissertation aims to investigate how this condition has consolidated over time and possible ways to combat it. The second part of the text shows an investigation about the ways to highlight the above-mentioned transformations imposed on the natural environment. For this, a series of techniques and visualization resources are presented, through which it is possible to reconstitute urbanization processes in a computational environment. The hypothesis is that this type of visual resource has great potential to aid in the understanding and criticism of the forms of space production. Although the objective of this research is not to directly reverse the alienation from nature, the method now being developed is a further step in the search for recognition of the spaces in which we live. The last part of the work is dedicated to the presentation of experiments with exercises performed with three groups of students. These exercises consisted in placing groups of students to design fictitious cities in places that today correspond to those of consolidated cities: Belo Horizonte and Sete Lagoas, both in Minas Gerais. The exercises proved to be efficient (revealing) in helping students, by comparing the representations of the actual city and the projected city, to perceive aspects of the concrete world hitherto difficult for them to recognize. The recognition of the physical space, followed by the rapprochement with the natural environment is a fundamental step for the future guarantee of the spatial quality of the cities.